The Influence of Humidity on Electron Transport Parameters and Insulation Performance of Air - An, Yunzhu; Su, Menghan; Hu, Yuanchao; Hu, Shangmao; Huang, Tao; He, Baina; Yang, Minghao; Yin, Kaiqiang; Lin, Yitong (Frontiers in Energy Research, 2022)
The environmental conditions affect the external insulation performance of power equipment. In order to study the physical characteristics of air discharge, the microscopic process of electron–molecule collision in the air based on the Boltzmann equation has been studied in this paper. The influence of humidity on the air gap insulation performance was also analyzed. The calculation results show that with the temperature 300 K and the pressure 1.0 atm, the electron energy distribution function and electron transport parameters varied with the air relative humidity. As the air relative humidity is increased by each 30%, the average electron energy decreases by about 0.2 eV, the reduced electron mobility decreases by about 0.25 × 1023 [1/(V·m·s)], the reduced electron diffusion coefficient decreases by about 0.2 × 1024 [1/(m s)], and the effective ionization coefficient decreases by about 4 × 10−24 m2. As the air relative humidity increases from 0% to 60%, the critical breakdown electric field increases by 1.22 kV/cm.